Beyond NAMs versus animal models: Context of use as the governing framework for integrated nonclinical strategies in drug development - Stefano Gaburro; Brian Berridge; Nicholas W. Kelley; Eckhard von Keutz; Marc Ferrer; Clive Roper; Michael J. Fossler; Jeffrey J. Bajramovic; Jean-Pierre Valentin; Timothy McGovern; Todd Bourcier; Ronald L. Wange; et al. (Regulatory Toxicology and Pharmacology, 2026)

Differential motor unit firing rate and hypertrophic adaptations of the vastus lateralis despite similar strength increases following high-load versus combined high- and low-load resistance training interventions - Alex A. Olmos; Daniel J. Lawson; Stephanie A. Sontag; Lyric D. Richardson; Brenden L. Roth; Sunggun Jeon; Allen L. Redinger; Sean M. Gamache; Michael A. Trevino (Experimental Brain Research, 2026)

Water volumes, heat flow, and solute discharge from Old Faithful Geyser eruptions, Yellowstone National Park, USA - Shaul Hurwitz; R. Blaine McCleskey; Maxwell L. Rudolph; Sara Peek; David A. Roth; Melissa Schott-Atkins; Michael Manga; Kiernan F. Folz Donahue; Mara H. Reed; Jefferson D.G. Hungerford (Journal of Volcanology and Geothermal Research, 2026)

Nasal hormone administration can support ambystomid salamander ex situ conservation breeding programs - Devin M. Chen; Carrie K. Kouba; Terri L. Roth; Peter J. Allen; Nucharin Songsasen; Andrew J. Kouba (Journal for Nature Conservation, 2026)

Oh deer! Videography reveals a range of defensive behaviors against a cervid by a ground‐nesting bird - Kylie L. Brunette; Amber M. Roth; Rachel L. Darling; Michael L. Peters; Erik J. Blomberg (Ecology, 2026)

Variability in Fecundity–Body Size Relationships for Atlantic Salmon Associated With Body Condition and Life History - Tara L. Imlay; Cindy Breau; Julien April; J. Brian Dempson; John Hayward; Jason LeBlanc; Jenny E. Reid; David Roth; Jamie T. Vallis; Travis E. Van Leeuwen; Laura K. Weir (Fisheries Management and Ecology, 2026)
While body size is the primary driver of fecundity, other factors may contribute to variation in these relationships. Anadromous populations of Atlantic salmon ( Salmo salar ) have diverse life histories, and fisheries management relies on accurate fecundity estimates. We used Bayesian hierarchical models to determine the relationship between fecundity and fork length, and other life‐history characteristics, for 25 spawning populations throughout Eastern Canada. Fecundity was best modeled at the river level, increased with body size and condition, and decreased with mean egg diameter. Fecundity was higher for individuals that spent fewer years in freshwater as juveniles, and for consecutive repeat spawners compared with first‐time (or maiden) spawners that spent 1 year in the ocean. Lastly, there was interannual variability in the fecundity–body size relationship. These relationships should be used in conjunction with data on recent changes in body size and/or life‐history traits of populations to inform stock management.

Correction: The influence of high-load and combined high- and low-load resistance training on electromyographic behavior during an absolute muscular endurance task - Alex A. Olmos; Stephanie A. Sontag; Daniel J. Lawson; Lyric D. Richardson; Brenden L. Roth; Sunggun Jeon; Jaiden C. Smith; Allen L. Redinger; Michael A. Trevino (European Journal of Applied Physiology, 2026)

The effect of muscle oxygenation on neuromuscular efficiency and force complexity - Petra Kis; Colin W. Kipper; Kylie N. Burleson; Brenden L. Roth; Jerome Hausselle; Joshua L. Keller; Shane M. Hammer (European Journal of Applied Physiology, 2026)

The collective application of shorebird tracking data to conservation - Autumn‐Lynn Harrison; Candace Stenzel; Alexandra Anderson; Jessica Howell; Richard B. Lanctot; Marley Aikens; Joaquín Aldabe; Liam A. Berigan; Joël Bêty; Erik Blomberg; Juliana Bosi de Almeida; Andy J. Boyce; et al. (Conservation Biology, 2026)
Addressing urgent conservation issues, such as the drastic declines of North American migratory birds, requires creative, evidence‐based, efficient, and collaborative approaches. The abundance of over 50% of monitored North American shorebird populations has declined by over 50% since 1980. To address these declines, we developed a partnership of scientists and practitioners called the Shorebird Science and Conservation Collective (hereafter the collective ). The collective was founded to translate the combined findings of shorebird tracking data into on‐the‐ground conservation action. With advice from an advisory group, the collective acts as an intermediary whereby dedicated staff collate and analyze data contributions from scientists to support knowledge requests from conservation practitioners. In its first three years, data contributions from 75 organizations include over 7.1 million shorebird observations forming movement paths of 3420 individuals representing 36 species tracked across the Americas and have informed 18 conservation projects spanning education, land and species management, land conservation, and policy requests. Others engaged in translational science from big data could consider similar knowledge‐sharing models that prioritize usable data products, foster collaborative engagement between science experts and practitioners, build focused communities around topics or taxonomic groups, and employ a proof‐of‐concept phase to develop scalable solutions while making progress toward long‐term funding to sustain impact. As the volume of scientific data continues to grow, intermediaries, such as the collective, can be vital liaisons to rapidly integrate and interpret research to support conservation action. Dedicated to the memory of Shiloh Schulte and his conservation achievements for shorebirds.

Ocean acidification in Canada: the current state of knowledge and pathways for action - Kristina M. Barclay; Helen J. Gurney-Smith; Mohamed Ahmed; James R. Christian; Frédéric Cyr; Patrick J. Duke; Brent G. T. Else; Iria Gimenez; Martine Lizotte; M. Catherine Reader; Myron Roth; Krysten Rutherford; et al. (Frontiers in Marine Science, 2026)
Ocean acidification (OA) generally receives far less consideration than other climate stressors and related hazards, such as global warming and extreme weather events. Canada is uniquely vulnerable to OA given its extensive coastal oceans, the oceanographic processes in its three basins, accelerated warming and sea-ice melt, and extensive coastal communities and maritime economic sectors. Canada’s coastline is also home to extensive and diverse First Nations peoples with distinct histories, rights, title, laws, governance and whose traditions and cultures are extrinsically linked to the sea. However, there are currently very limited pathways to support OA action, mitigation, and/or adaptation in Canada, particularly at the policy level. Here, we present a first synthesis of the current state of OA knowledge across Canada's Pacific, Arctic, and Atlantic regions, including monitoring, modelling, biological responses, socioeconomic and policy perspectives, and examples of existing OA actions and efforts at local and provincial levels. We also suggest a step-wise pathway for actions to enhance the coordinated filling of OA knowledge gaps and integration of OA knowledge into decision-making frameworks. The goals of these recommendations are to improve our ability to respond to OA in Canada, and minimize risks to coastal marine environments and ecosystems, vulnerable sectors, and communities.

Cognitive Intra-individual Variability in Cognitively Healthy APOE ε4 Carriers, Mild Cognitive Impairment, and Alzheimer’s Disease: a Meta-analysis - Stephen L. Aita; Victor A. Del Bene; Donald L. Knapp; Claire E. Demming; Vasilios C. Ikonomou; Tyler Owen; Ivan A. Campbell; Bailey N. Wagaman; Nicholas C. Borgogna; Joshua E. Caron; Robert M. Roth; Benjamin D. Hill (Neuropsychology Review, 2025)

The influence of high-load and combined high- and low-load resistance training on electromyographic behavior during an absolute muscular endurance task - Alex A. Olmos; Stephanie A. Sontag; Daniel J. Lawson; Lyric D. Richardson; Brenden L. Roth; Sunggun Jeon; Jaiden C. Smith; Allen L. Redinger; Michael A. Trevino (European Journal of Applied Physiology, 2025)

Air pollution exposure assessment for preschool children: Addressing spatial and temporal variations and social inequities - Å.K. Watne; M. Azzouz; P. Molnar; L. Stockfelt; J. Lindén; E. Johansson; M. Laurelin; T. Wisell; H. Lundström; A. Roth; S. Jutterström; J. Moldanova; et al. (Journal of Environmental Management, 2025)

Long-term field study on corn response to sulfur fertilization in Iowa, USA - Cecilia Crespo; John L. Kovar; Chad E. Hart; Richard T. Roth; Peter L. O’Brien; Sabrina J. Ruis (Field Crops Research, 2025)

Development of diagnostic markers for the disease susceptibility gene Tsn1 in wheat reveals novel resistance alleles and a new locus required for ToxA sensitivity - Katherine L. D. Running; Krishna Acharya; Tiana M. Roth; Gurminder Singh; Agnes Szabo-Hever; Amanda R. Peters Haugrud; Jason D. Fiedler; Timothy L. Friesen; Justin D. Faris (Theoretical and Applied Genetics, 2025)

GRANDlib: A simulation pipeline for the Giant Radio Array for Neutrino Detection (GRAND) - R. Alves Batista; A. Benoit-Lévy; T. Bister; M. Bohacova; M. Bustamante; W. Carvalho; Y. Chen; L. Cheng; S. Chiche; J.M. Colley; P. Correa; N. Cucu Laurenciu; et al. (Computer Physics Communications, 2025)

Using hyperspectral and thermal imagery to monitor stress of Southern California plant species during the 2013–2015 drought - Susan K. Meerdink; Dar A. Roberts; Jennifer Y. King; Keely L. Roth; Paul D. Gader; Kelly K. Caylor (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Unlocking the epigenome: Stress and exercise induced Bdnf regulation in the prefrontal cortex - Taylor S. Campbell; Katelyn Donoghue; Tania L. Roth (Neurotoxicology and Teratology, 2024)

Identifying predictors of translocation success in rare plant species - Joe Bellis; Oyomoare Osazuwa‐Peters; Joyce Maschinski; Matthew J. Keir; Elliott W. Parsons; Thomas N. Kaye; Michael Kunz; Jennifer Possley; Eric Menges; Stacy A. Smith; Daniela Roth; Debbie Brewer; et al. (Conservation Biology, 2024)
The fundamental goal of a rare plant translocation is to create self‐sustaining populations with the evolutionary resilience to persist in the long term. Yet, most plant translocation syntheses focus on a few factors influencing short‐term benchmarks of success (e.g., survival and reproduction). Short‐term benchmarks can be misleading when trying to infer future growth and viability because the factors that promote establishment may differ from those required for long‐term persistence. We assembled a large ( n = 275) and broadly representative data set of well‐documented and monitored (7.9 years on average) at‐risk plant translocations to identify the most important site attributes, management techniques, and species’ traits for six life‐cycle benchmarks and population metrics of translocation success. We used the random forest algorithm to quantify the relative importance of 29 predictor variables for each metric of success. Drivers of translocation outcomes varied across time frames and success metrics. Management techniques had the greatest relative influence on the attainment of life‐cycle benchmarks and short‐term population trends, whereas site attributes and species’ traits were more important for population persistence and long‐term trends. Specifically, large founder sizes increased the potential for reproduction and recruitment into the next generation, whereas declining habitat quality and the outplanting of species with low seed production led to increased extinction risks and a reduction in potential reproductive output in the long‐term, respectively. We also detected novel interactions between some of the most important drivers, such as an increased probability of next‐generation recruitment in species with greater seed production rates, but only when coupled with large founder sizes. Because most significant barriers to plant translocation success can be overcome by improving techniques or resolving site‐level issues through early intervention and management, we suggest that by combining long‐term monitoring with adaptive management, translocation programs can enhance the prospects of achieving long‐term success.

Geographic distribution of the Cross Seamount beaked whale based on acoustic detections - Jennifer L. K. McCullough; E. Elizabeth Henderson; Jennifer S. Trickey; Jay Barlow; Simone Baumann‐Pickering; Roanne Manzano‐Roth; Gabriela Alongi; Stephen Martin; Selene Fregosi; David K. Mellinger; Holger Klinck; Angela R. Szesciorka; et al. (Marine Mammal Science, 2024)
Beaked whales produce frequency‐modulated echolocation pulses that appear to be species‐specific, allowing passive acoustic monitoring to play a role in understanding spatio‐temporal patterns. The Cross Seamount beaked whale is known only from its unique echolocation signal (BWC) with no confirmed species identification. This beaked whale spans the Pacific Ocean from the Mariana Archipelago to Baja California, Mexico, south to the equator, but only as far north as latitude 29°N. Within these warm waters, 92% of BWC detections occurred at night, 6% during crepuscular periods, and only 2% during daylight hours. Detections of BWC signals on drifting recorders with a vertical hydrophone array at 150 m depth demonstrated that foraging often occurred shallow in the water column (

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Ganymede's atmosphere as constrained by HST/STIS observations - F. Leblanc; L. Roth; J.Y. Chaufray; R. Modolo; M. Galand; N. Ivchenko; G. Carnielli; C. Baskevitch; A. Oza; A.L.E. Werner (Icarus, 2023)

Modeling the impacts of temperature during nesting seasons on Loggerhead (Caretta caretta) Sea Turtle populations in South Florida - Spencer Catron; Sarah Roth; Francesca Zumpano; Jason Bintz; James A. Fordyce; Suzanne Lenhart; Debra L. Miller; Jeanette Wyneken (Ecological Modelling, 2023)

Description of two cultivated and two uncultivated new Salinibacter species, one named following the rules of the bacteriological code: Salinibacter grassmerensis sp. nov.; and three named following the rules of the SeqCode: Salinibacter pepae sp. nov., Salinibacter abyssi sp. nov., and Salinibacter pampae sp. nov. - Tomeu Viver; Roth E. Conrad; Marianna Lucio; Mourad Harir; Mercedes Urdiain; Juan F. Gago; Ana Suárez-Suárez; Esteban Bustos-Caparros; Rodrigo Sanchez-Martinez; Eva Mayol; Federico Fassetta; Jinfeng Pang; et al. (Systematic and Applied Microbiology, 2023)

Multiple sources implicated in the red swamp crayfish invasion in Michigan, USA - N. M. Sard; K. R. Smith; B. M. Roth; L. R. Nathan; S. J. Herbst; K. T. Scribner (Biological Invasions, 2023)

The 2022 Diadema antillarum die-off event: Comparisons with the 1983-1984 mass mortality - Alwin Hylkema; Kimani Kitson-Walters; Patricia R. Kramer; Joshua T. Patterson; Lynnette Roth; Moriah L. B. Sevier; Maria Vega-Rodriguez; Matthew M. Warham; Stacey M. Williams; Judith C. Lang (Frontiers in Marine Science, 2023)
The 1983-1984 die-off of the long-spined sea urchin Diadema antillarum stands out as a catastrophic marine event because of its detrimental effects on Caribbean coral reefs. Without the grazing activities of this key herbivore, turf and macroalgae became the dominant benthic group, inhibiting coral recruitment and compromising coral reef recovery from other disturbances. In the decades that followed, recovery of D. antillarum populations was slow to non-existent. In late January 2022, a new mass mortality of D. antillarum was first observed in the U.S. Virgin Islands. We documented the spread and extent of this new die-off using an online survey. Infected individuals were closely monitored in the lab to record signs of illness, while a large population on Saba, Dutch Caribbean, was surveyed weekly before and during mortality to determine the lethality of this event. Within four months the die-off was distributed over 1,300 km from north to south and 2,500 km east to west. Whereas the 1983-1984 die-off advanced mostly with the currents, the 2022 event has appeared far more quickly in geographically distant areas. First die-off observations in each jurisdiction were often close to harbor areas, which, together with their rapid appearance, suggests that anthropogenic factors may have contributed to the spread of the causative agent. The signs of illness in sick D. antillarum were very similar to those recorded during the 1983-1984 die-off: lack of tube feet control, slow spine reaction followed by their loss, and necrosis of the epidermis were observed in both lab and wild urchins. Affected populations succumbed fast; within a month of the first signs of illness, a closely monitored population at Saba, Dutch Caribbean, had decreased from 4.05 individuals per m 2 to 0.05 individuals per m 2 . Lethality can therefore be as high as 99%. The full extent of the 2022 D. antillarum die-off event is not currently known. The slower spread in the summer of 2022 might indicate that the die-off is coming to a (temporary) standstill. If this is the case, some populations will remain unaffected and potentially supply larvae to downstream areas and augment natural recovery processes. In addition, several D. antillarum rehabilitation approaches have been developed in the past decade and some are ready for large scale implementation. However, active conservation and restoration should not distract from the primary goal of identifying a cause and, if possible, implementing actions to decrease the likelihood of future D. antillarum die-off events.

Experimental natural disturbance-based silviculture systems maintain mature forest bird assemblage long-term in Maine (USA) - Carl K. Pohlman; Amber M. Roth; Mitschka J. Hartley; Malcolm L. Hunter; Brian J. McGill; Robert S. Seymour (Forest Ecology and Management, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Targeting Sagebrush (Artemisia Spp.) Restoration Following Wildfire with Greater Sage-Grouse (Centrocercus Urophasianus) Nest Selection and Survival Models - Cali L. Roth; Shawn T. O’Neil; Peter S. Coates; Mark A. Ricca; David A. Pyke; Cameron L. Aldridge; Julie A. Heinrichs; Shawn P. Espinosa; David J. Delehanty (Environmental Management, 2022)
Unprecedented conservation efforts for sagebrush ( Artemisia spp.) ecosystems across the western United States have been catalyzed by risks from escalated wildfire activity that reduces habitat for sagebrush-obligate species such as Greater Sage-Grouse ( Centrocercus urophasianus ). However, post-fire restoration is challenged by spatial variation in ecosystem processes influencing resilience to disturbance and resistance to non-native invasive species, and spatial and temporal lags between slower sagebrush recovery processes and faster demographic responses of sage-grouse to loss of important habitat. Decision-support frameworks that account for these factors can help users strategically apply restoration efforts by predicting short and long-term ecological benefits of actions. Here, we developed a framework that strategically targets burned areas for restoration actions (e.g., seeding or planting sagebrush) that have the greatest potential to positively benefit sage-grouse populations through time. Specifically, we estimated sagebrush recovery following wildfire and risk of non-native annual grass invasion under four scenarios: passive recovery, grazing exclusion, active restoration with seeding, and active restoration with seedling transplants. We then applied spatial predictions of integrated nest site selection and survival models before wildfire, immediately following wildfire, and at 30 and 50 years post-wildfire based on each restoration scenario and measured changes in habitat. Application of this framework coupled with strategic planting designs aimed at developing patches of nesting habitat may help increase operational resilience for fire-impacted sagebrush ecosystems.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The role of oxygen in stimulating methane production in wetlands - Jared L. Wilmoth; Jeffra K. Schaefer; Danielle R. Schlesinger; Spencer W. Roth; Patrick G. Hatcher; Julie K. Shoemaker; Xinning Zhang (Global Change Biology, 2021)
Methane (CH 4 ), a potent greenhouse gas, is the second most important greenhouse gas contributor to climate change after carbon dioxide (CO 2 ). The biological emissions of CH 4 from wetlands are a major uncertainty in CH 4 budgets. Microbial methanogenesis by Archaea is an anaerobic process accounting for most biological CH 4 production in nature, yet recent observations indicate that large emissions can originate from oxygenated or frequently oxygenated wetland soil layers. To determine how oxygen (O 2 ) can stimulate CH 4 emissions, we used incubations of Sphagnum peat to demonstrate that the temporary exposure of peat to O 2 can increase CH 4 yields up to 2000‐fold during subsequent anoxic conditions relative to peat without O 2 exposure. Geochemical (including ion cyclotron resonance mass spectrometry, X‐ray absorbance spectroscopy) and microbiome (16S rDNA amplicons, metagenomics) analyses of peat showed that higher CH 4 yields of redox‐oscillated peat were due to functional shifts in the peat microbiome arising during redox oscillation that enhanced peat carbon (C) degradation. Novosphingobium species with O 2 ‐dependent aromatic oxygenase genes increased greatly in relative abundance during the oxygenation period in redox‐oscillated peat compared to anoxic controls. Acidobacteria species were particularly important for anaerobic processing of peat C, including in the production of methanogenic substrates H 2 and CO 2 . Higher CO 2 production during the anoxic phase of redox‐oscillated peat stimulated hydrogenotrophic CH 4 production by Methanobacterium species. The persistence of reduced iron (Fe(II)) during prolonged oxygenation in redox‐oscillated peat may further enhance C degradation through abiotic mechanisms (e.g., Fenton reactions). The results indicate that specific functional shifts in the peat microbiome underlie O 2 enhancement of CH 4 production in acidic, Sphagnum ‐rich wetland soils. They also imply that understanding microbial dynamics spanning temporal and spatial redox transitions in peatlands is critical for constraining CH 4 budgets; predicting feedbacks between climate change, hydrologic variability, and wetland CH 4 emissions; and guiding wetland C management strategies.

The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

Psychometric utility of the international HIV dementia scale and Montreal Cognitive Assessment in HIV-associated asymptomatic neurocognitive impairment - Stephen L. Aita; Quanhathai Kaewpoowat; Saowaluck Yasri; Amaraporn Rerkasem; Kittipan Rerkasem; Janejit Choovuthayakorn; Somsanguan Ausayakhun; Kevin Robertson; Robert M. Roth; Nathaniel M. Robbins (Journal of NeuroVirology, 2021)

Correlates of bird collisions with buildings across three North American countries - Jared A. Elmore; Stephen B. Hager; Bradley J. Cosentino; Timothy J. O'Connell; Corey S. Riding; Michelle L. Anderson; Marja H. Bakermans; Than J. Boves; David Brandes; Eric M. Butler; Michael W. Butler; Nicolette L. Cagle; et al. (Conservation Biology, 2021)
Collisions with buildings cause up to 1 billion bird fatalities annually in the United States and Canada. However, efforts to reduce collisions would benefit from studies conducted at large spatial scales across multiple study sites with standardized methods and consideration of species‐ and life‐history‐related variation and correlates of collisions. We addressed these research needs through coordinated collection of data on bird collisions with buildings at sites in the United States (35), Canada (3), and Mexico (2). We collected all carcasses and identified species. After removing records for unidentified carcasses, species lacking distribution‐wide population estimates, and species with distributions overlapping fewer than 10 sites, we retained 269 carcasses of 64 species for analysis. We estimated collision vulnerability for 40 bird species with ≥2 fatalities based on their North American population abundance, distribution overlap in study sites, and sampling effort. Of 10 species we identified as most vulnerable to collisions, some have been identified previously (e.g., Black‐throated Blue Warbler [ Setophaga caerulescens ]), whereas others emerged for the first time (e.g., White‐breasted Nuthatch [ Sitta carolinensis ]), possibly because we used a more standardized sampling approach than past studies. Building size and glass area were positively associated with number of collisions for 5 of 8 species with enough observations to analyze independently. Vegetation around buildings influenced collisions for only 1 of those 8 species (Swainson's Thrush [ Catharus ustulatus ]). Life history predicted collisions; numbers of collisions were greatest for migratory, insectivorous, and woodland‐inhabiting species. Our results provide new insight into the species most vulnerable to building collisions, making them potentially in greatest need of conservation attention to reduce collisions and into species‐ and life‐history‐related variation and correlates of building collisions, information that can help refine collision management.

Protease Inhibitors, Saquinavir and Darunavir, Inhibit Oligodendrocyte Maturation: Implications for Lysosomal Stress - Lindsay Festa; Lindsay M. Roth; Brigid K. Jensen; Jonathan D. Geiger; Kelly L. Jordan-Sciutto; Judith B. Grinspan (Journal of Neuroimmune Pharmacology, 2021)

Application and clinical impact of the RESIST-4 O.K.N.V. rapid diagnostic test for carbapenemase detection in blood cultures and clinical samples - Sophie Roth; Fabian K. Berger; Andreas Link; Anna Nimmesgern; Philipp M. Lepper; Niels Murawski; Jörg T. Bittenbring; Sören L. Becker (European Journal of Clinical Microbiology & Infectious Diseases, 2021)
Invasive infections caused by carbapenemase-producing bacteria are associated with excess mortality. We applied a rapid diagnostic test (RDT) on clinical samples with an elevated likelihood of carbapenemase-producing bacteria and documented its impact on antibiotic treatment decisions. Among 38 patients, twelve tested positive for infections caused by carbapenemase-producing bacteria (31.6%), mainly in blood cultures. KPC ( n = 10) was more frequent than OXA-48 ( n = 2). RDT-based carbapenemase detection led to a treatment modification to ceftazidime/avibactam-containing regimens in all patients before detailed antibiotic testing results became available. Eleven patients (92%) survived the acute infection, whereas one patient with a ceftazidime/avibactam- and colistin-resistant OXA-48-positive isolate died.

Typologies of individuals vulnerable to insomnia: a two-step cluster analysis - Daniel Ruivo Marques; Ana Allen Gomes; Vanda Clemente; Christopher L. Drake; Thomas Roth; Charles M. Morin; Maria Helena Pinto de Azevedo (Sleep and Biological Rhythms, 2021)

Modeling the Supporting Ecosystem Services of Depressional Wetlands in Agricultural Landscapes - David M. Mushet; Cali L. Roth (Wetlands, 2020)
We explored how a geographic information system modeling approach could be used to quantify supporting ecosystem services related to the type, abundance, and distribution of landscape components. Specifically, we use the Integrated Valuation of Ecosystem Services and Tradeoffs model to quantify habitats that support amphibians and birds, floral resources that support pollinators, native-plant communities that support regional biodiversity, and above- and below-ground carbon stores in the Des Moines Lobe ecoregion of the U.S. We quantified services under two scenarios, one that represented the 2012 Des Moines Lobe landscape, and one that simulated the conversion to crop production of wetlands and surrounding uplands conserved under the USDA Agricultural Conservation Easement Program (ACEP). While ACEP easements only covered 0.35% of the ecoregion, preserved wetlands and grasslands provided for 19,020 ha of amphibian habitat, 21,462 ha of grassland-bird habitat, 18,798 ha of high-quality native wetland plants, and 27,882 ha of floral resources for pollinators. Additionally, ACEP protected lands stored 257,722 t of carbon that, if released, would result in costs in excess of 45-million USD. An integrated approach using results from a GIS-based model in combination with process-based model quantifications will facilitate more informed decisions related to ecosystem service tradeoffs.

Rethinking the interplay between affluence and vulnerability to aid climate change adaptive capacity - Christine Eriksen; Gregory L. Simon; Florian Roth; Shefali Juneja Lakhina; Ben Wisner; Carolina Adler; Frank Thomalla; Anna Scolobig; Kate Brady; Michael Bründl; Florian Neisser; Maree Grenfell; et al. (Climatic Change, 2020)
Affluence and vulnerability are often seen as opposite sides of a coin—with affluence generally understood as reducing forms of vulnerability through increased resilience and adaptive capacity. However, in the context of climate change and an increase in associated hazards and disasters, we suggest the need to re-examine this dynamic relationship—a complex association we define here as the Affluence–Vulnerability Interface (AVI). We review research in different national contexts to show how a more nuanced understanding of the AVI can (a) problematize the notion that increasing material affluence necessarily has a mitigating influence on social vulnerability, (b) extend our analysis of social vulnerability beyond low-income regions to include affluent contexts and (c) improve our understanding of how psychosocial characteristics influence people’s vulnerability. Finally, we briefly outline three methodological approaches that we believe will assist future engagement with the AVI.

Reassessing Potential for Exotic Larch in Northern United States - David I Maass; Lloyd C Irland; James L Anderson; Kenneth M Laustsen; Michael S Greenwood; Brian E Roth (Journal of Forestry, 2020)
Abstract Field measurements of operational plantations and research plots demonstrate that growth rates of exotic larches in unmanaged stands can exceed 12 m3 per hectare per year in Maine and elsewhere. This paper briefly reviews the recent history of exotic larch (Larix decidua, L. kaempferi, and L. × marschlinsii) in northeastern United States and Canada. Stands can be commercially thinned as early as 15 years; further thinnings add to significant volume accumulation, based on stand table projections. Genetic development of the hybrid (L. × marschlinsii) could yield additional volume. Even at current low stumpage values, exotic larch plantations offer positive returns at realistic discount rates. In map form, we report a current inventory of known trials and operational plantings across the Northern United States, including adjacent Canada.

Concurrent isolation of hepatic stem cells and hepatocytes from the human liver - Serene M. L. Lee; Cristina Bertinetti-Lapatki; Tobias S. Schiergens; Karl-Walter Jauch; Adrian B. Roth; Wolfgang E. Thasler (In Vitro Cellular & Developmental Biology - Animal, 2020)
Hepatocytes differentiated from induced pluripotent stem cells or stem cells have the potential to be representative in vitro models of the human liver for research as well as early safety assessment programs. However, up until now, there has been no definitive proof that differentiated hepatocytes recapitulate the phenotype and functional characteristics of primary hepatocytes from the same individual. Thus, a method for the concurrent isolation of hepatocytes and hepatic stem cells is presented here to provide the cells necessary for the evaluation of the required benchmarking. The method presented here generated high-quality hepatocytes with a purity of 94 ± 1% and a high percentage viability of 79 ± 2%. Furthermore, the hepatic stem cells isolated were found to be actively proliferating and have a purity of 98 ± 1%. Thus, these isolated cells can be used as a powerful tool for the validation of differentiated hepatocyte in vitro models.

Electroplating for chromium removal from tannery wastewater - G. S. da Silva; F. A. dos Santos; G. Roth; C. L. C. Frankenberg (International Journal of Environmental Science and Technology, 2020)

Ecophysiology of mesophotic reef‐building corals in Hawai‘i is influenced by symbiont–host associations, photoacclimatization, trophic plasticity, and adaptation - Jacqueline L. Padilla‐Gamiño; Melissa S. Roth; Lisa J. Rodrigues; Christina J. Bradley; Robert R. Bidigare; Ruth D. Gates; Celia M. Smith; Heather L. Spalding (Limnology and Oceanography, 2019)
Mesophotic reef corals remain largely unexplored in terms of the genetic adaptations and physiological mechanisms to acquire, allocate, and use energy for survival and reproduction. In the Hawaiian Archipelago, the Leptoseris species complex form the most spatially extensive mesophotic coral ecosystem known and provide habitat for a unique community. To study how the ecophysiology of Leptoseris species relates to symbiont–host specialization and understand the mechanisms responsible for coral energy acquisition in extreme low light environments, we examined Symbiodinium (endosymbiotic dinoflagellate) photobiological characteristics and the lipids and isotopic signatures from Symbiodinium and coral hosts over a depth‐dependent light gradient (55–7 μ mol photons m −2 s −1 , 60–132 m). Clear performance differences demonstrate different photoadaptation and photoacclimatization across this genus. Our results also show that flexibility in photoacclimatization depends primarily on Symbiodinium type. Colonies harboring Symbiodinium sp. COI‐2 showed significant increases in photosynthetic pigment content with increasing depth, whereas colonies harboring Symbiodinium spp. COI‐1 and COI‐3 showed variability in pigment composition, yield measurements for photosystem II, as well as size and density of Symbiodinium cells. Despite remarkable differences in photosynthetic adaptive strategies, there were no significant differences among lipids of Leptoseris species with depth. Finally, isotopic signatures of both host and Symbiodinium changed with depth, indicating that coral colonies acquired energy from different sources depending on depth. This study highlights the complexity in physiological adaptations within this symbiosis and the different strategies used by closely related mesophotic species to diversify energy acquisition and to successfully establish and compete in extreme light‐limited environments.

Changes in the distribution of Michigan crayfishes and the influence of invasive rusty crayfish (Faxonius rusticus) on native crayfish substrate associations - Kelley R. Smith; Brian M. Roth; Michael L. Jones; Daniel B. Hayes; Seth J. Herbst; Nicholas Popoff (Biological Invasions, 2019)

Sex Differences in Early Postnatal Microglial Colonization of the Developing Rat Hippocampus Following a Single-Day Alcohol Exposure - M. J. Ruggiero; K. E. Boschen; T. L. Roth; A. Y. Klintsova (Journal of Neuroimmune Pharmacology, 2018)

Integration of sudden death syndrome resistance loci in the soybean genome - Hao-Xun Chang; Mitchell G. Roth; Dechun Wang; Silvia R. Cianzio; David A. Lightfoot; Glen L. Hartman; Martin I. Chilvers (Theoretical and Applied Genetics, 2018)

Climate change effects on livestock in the Northeast US and strategies for adaptation - A. N. Hristov; A. T. Degaetano; C. A. Rotz; E. Hoberg; R. H. Skinner; T. Felix; H. Li; P. H. Patterson; G. Roth; M. Hall; T. L. Ott; L. H. Baumgard; et al. (Climatic Change, 2018)

Mainstreaming the social sciences in conservation - Nathan J. Bennett; Robin Roth; Sarah C. Klain; Kai M. A. Chan; Douglas A. Clark; Georgina Cullman; Graham Epstein; Michael Paul Nelson; Richard Stedman; Tara L. Teel; Rebecca E. W. Thomas; Carina Wyborn; et al. (Conservation Biology, 2017)
Despite broad recognition of the value of social sciences and increasingly vocal calls for better engagement with the human element of conservation, the conservation social sciences remain misunderstood and underutilized in practice. The conservation social sciences can provide unique and important contributions to society's understanding of the relationships between humans and nature and to improving conservation practice and outcomes. There are 4 barriers—ideological, institutional, knowledge, and capacity—to meaningful integration of the social sciences into conservation. We provide practical guidance on overcoming these barriers to mainstream the social sciences in conservation science, practice, and policy. Broadly, we recommend fostering knowledge on the scope and contributions of the social sciences to conservation, including social scientists from the inception of interdisciplinary research projects, incorporating social science research and insights during all stages of conservation planning and implementation, building social science capacity at all scales in conservation organizations and agencies, and promoting engagement with the social sciences in and through global conservation policy‐influencing organizations. Conservation social scientists, too, need to be willing to engage with natural science knowledge and to communicate insights and recommendations clearly. We urge the conservation community to move beyond superficial engagement with the conservation social sciences. A more inclusive and integrative conservation science—one that includes the natural and social sciences—will enable more ecologically effective and socially just conservation. Better collaboration among social scientists, natural scientists, practitioners, and policy makers will facilitate a renewed and more robust conservation. Mainstreaming the conservation social sciences will facilitate the uptake of the full range of insights and contributions from these fields into conservation policy and practice.

Lipid removal and acidification affect nitrogen and carbon stable isotope ratios of beluga whales (Delphinapterus leucas) and their potential prey species in the Beaufort Sea ecosystem - Emily S. Choy; James D. Roth; Lisa L. Loseto (Marine Biology, 2016)

Mismatch repair deficiency concordance between primary colorectal cancer and corresponding metastasis - Sigurdis Haraldsdottir; Rachel Roth; Rachel Pearlman; Heather Hampel; Christina A. Arnold; Wendy L. Frankel (Familial Cancer, 2016)

Applicability of APSIM to capture the effectiveness of irrigation management decisions in rice-based cropping sequence in the Upper-Gangetic Plains of India - N. Subash; M. Shamim; V. K. Singh; B. Gangwar; B. Singh; D. S. Gaydon; C. H. Roth; P. L. Poulton; A. K. Sikka (Paddy and Water Environment, 2015)

Glutamate Release Machinery Is Altered in the Frontal Cortex of Rats with Experimental Autoimmune Encephalomyelitis - Natalí L. Chanaday; A. Alejandro Vilcaes; Ana L. de Paul; Alicia I. Torres; Alicia L. Degano; German A. Roth (Molecular Neurobiology, 2015)

Genome and physiology of the ascomycete filamentous fungus X eromyces bisporus , the most xerophilic organism isolated to date - Su‐lin L. Leong; Henrik Lantz; Olga V. Pettersson; Jens C. Frisvad; Ulf Thrane; Hermann J. Heipieper; Jan Dijksterhuis; Manfred Grabherr; Mats Pettersson; Christian Tellgren‐Roth; Johan Schnürer (Environmental Microbiology, 2015)
Summary X eromyces bisporus can grow on sugary substrates down to 0.61, an extremely low water activity. Its genome size is approximately 22 Mb . Gene clusters encoding for secondary metabolites were conspicuously absent; secondary metabolites were not detected experimentally. Thus, in its ‘dry’ but nutrient‐rich environment, X . bisporus appears to have relinquished abilities for combative interactions. Elements to sense/signal osmotic stress, e.g. HogA pathway, were present in X . bisporus . However, transcriptomes at optimal (∼ 0.89) versus low a w (0.68) revealed differential expression of only a few stress‐related genes; among these, certain (not all) steps for glycerol synthesis were upregulated. X eromyces bisporus increased glycerol production during hypo‐ and hyper‐osmotic stress, and much of its wet weight comprised water and rinsable solutes; leaked solutes may form a protective slime. X eromyces bisporus and other food‐borne moulds increased membrane fatty acid saturation as water activity decreased. Such modifications did not appear to be transcriptionally regulated in X . bisporus ; however, genes modulating sterols, phospholipids and the cell wall were differentially expressed. X eromyces bisporus was previously proposed to be a ‘chaophile’, preferring solutes that disorder biomolecular structures. Both X . bisporus and the closely related xerophile, X erochrysium xerophilum , with low membrane unsaturation indices, could represent a phylogenetic cluster of ‘chaophiles’.

The opioid receptor pharmacology of GSK1521498 compared to other ligands with differential effects on compulsive reward-related behaviours - Eamonn Kelly; Stuart J. Mundell; Anna Sava; Adelheid L. Roth; Antonio Felici; Kay Maltby; Pradeep J. Nathan; Edward T. Bullmore; Graeme Henderson (Psychopharmacology, 2015)

Nanosecond pulsed electric fields modulate the expression of Fas/CD95 death receptor pathway regulators in U937 and Jurkat Cells - Larry E. Estlack; Caleb C. Roth; Gary L. Thompson; William A. Lambert; Bennett L. Ibey (Apoptosis, 2014)

Impact of raw pig slurry and pig farming practices on physicochemical parameters and on atmospheric N2O and CH4 emissions of tropical soils, Uvéa Island (South Pacific) - E. Roth; P. Gunkel-Grillon; L. Joly; X. Thomas; T. Decarpenterie; I. Mappe-Fogaing; C. Laporte-Magoni; N. Dumelié; G. Durry (Environmental Science and Pollution Research, 2014)

Multilocation Corn Stover Harvest Effects on Crop Yields and Nutrient Removal - Douglas L. Karlen; Stuart J. Birrell; Jane M. F. Johnson; Shannon L. Osborne; Thomas E. Schumacher; Gary E. Varvel; Richard B. Ferguson; Jeff M. Novak; James R. Fredrick; John M. Baker; John A. Lamb; Paul R. Adler; et al. (BioEnergy Research, 2014)

Deletion of the D domain of the human parainfluenza virus type 3 (HPIV3) PD protein results in decreased viral RNA synthesis and beta interferon (IFN-β) expression - Jason P. Roth; Joseph K.-K. Li; John D. Morrey; Dale L. Barnard; Almut H. Vollmer (Virus Genes, 2013)

Are all eggs created equal? A case study from the Hawaiian reef-building coral Montipora capitata - Jacqueline L. Padilla-Gamiño; Robert R. Bidigare; Daniel J. Barshis; Ada Alamaru; Laetitia Hédouin; Xavier Hernández-Pech; Frederique Kandel; Sherril Leon Soon; Melissa S. Roth; Lisa J. Rodrigues; Andrea G. Grottoli; Claudia Portocarrero; et al. (Coral Reefs, 2013)

Differential hippocampal gene expression is associated with climate‐related natural variation in memory and the hippocampus in food‐caching chickadees - V. V. Pravosudov; T. C. Roth; M. L. Forister; L. D. LaDage; R. Kramer; F. Schilkey; A. M. van der Linden (Molecular Ecology, 2013)
There is significant and often heritable variation in cognition and its underlying neural mechanisms, yet specific genetic contributions to such variation are not well characterized. Black‐capped chickadees present a good model to investigate the genetic basis of cognition because they exhibit tremendous climate‐related variation in memory, hippocampal morphology and neurogenesis rates throughout the North American continent, and these cognitive traits appear to have a heritable basis. We examined the hippocampal transcriptome profiles of laboratory‐reared chickadees from the two most divergent populations to test whether differential gene expression in the hippocampus is associated with population differences in spatial memory, hippocampal morphology and adult hippocampal neurogenesis rates. Using high‐resolution mRNA sequencing coupled to a de novo transcriptome assembly, we generated 23 295 consensus sequences, which predicted 16 206 protein sequences with 13 982 showing high similarity to known protein sequences or conserved hypothetical proteins in other species. Of these, we identified differential expression in nearly 380 genes, with 47 genes specifically linked to neurogenesis, apoptosis, synaptic function, and learning and memory processes. Many of the other differentially expressed genes, however, may be associated with other functions. Our study presents the first avian hippocampal transcriptome, and it is the first study identifying differential gene expression associated with natural variation in cognition and the hippocampus. Our results provide additional support to the hypothesis that population differences in memory, hippocampal morphology and neurogenesis in chickadees have likely resulted from natural selection that appears to act on memory and its underlying neural mechanisms.

Population genetic structure and its implications for adaptive variation in memory and the hippocampus on a continental scale in food‐caching black‐capped chickadees - V. V. Pravosudov; T. C. Roth; M. L. Forister; L. D. LaDage; T. M. Burg; M. J. Braun; B. S. Davidson (Molecular Ecology, 2012)
Food‐caching birds rely on stored food to survive the winter, and spatial memory has been shown to be critical in successful cache recovery. Both spatial memory and the hippocampus, an area of the brain involved in spatial memory, exhibit significant geographic variation linked to climate‐based environmental harshness and the potential reliance on food caches for survival. Such geographic variation has been suggested to have a heritable basis associated with differential selection. Here, we ask whether population genetic differentiation and potential isolation among multiple populations of food‐caching black‐capped chickadees is associated with differences in memory and hippocampal morphology by exploring population genetic structure within and among groups of populations that are divergent to different degrees in hippocampal morphology. Using mitochondrial DNA and 583 AFLP loci, we found that population divergence in hippocampal morphology is not significantly associated with neutral genetic divergence or geographic distance, but instead is significantly associated with differences in winter climate. These results are consistent with variation in a history of natural selection on memory and hippocampal morphology that creates and maintains differences in these traits regardless of population genetic structure and likely associated gene flow.

Role of kappa-opioid receptors in the effects of salvinorin A and ketamine on attention in rats - Christina L. Nemeth; Tracie A. Paine; Joseph E. Rittiner; Cécile Béguin; F. Ivy Carroll; Bryan L. Roth; Bruce M. Cohen; William A. Carlezon (Psychopharmacology, 2010)

Amisulpride is a potent 5-HT7 antagonist: relevance for antidepressant actions in vivo - Atheir I. Abbas; Peter B. Hedlund; Xi-Ping Huang; Thuy B. Tran; Herbert Y. Meltzer; Bryan L. Roth (Psychopharmacology, 2009)

Cryptic seedling herbivory by nocturnal introduced generalists impacts survival, performance of native and exotic plants - Sharon Y. Strauss; Maureen L. Stanton; Nancy C. Emery; Carrie A. Bradley; Alexandra Carleton; Dylan R. Dittrich-Reed; Olivia A. Ervin; Levi N. Gray; Andrew M. Hamilton; Jennifer Harrington Rogge; Skye D. Harper; Kimberley Cook Law; et al. (Ecology, 2009)
Although much of the theory on the success of invasive species has been geared at escape from specialist enemies, the impact of introduced generalist invertebrate herbivores on both native and introduced plant species has been underappreciated. The role of nocturnal invertebrate herbivores in structuring plant communities has been examined extensively in Europe, but less so in North America. Many nocturnal generalists (slugs, snails, and earwigs) have been introduced to North America, and 96% of herbivores found during a night census at our California Central Valley site were introduced generalists. We explored the role of these herbivores in the distribution, survivorship, and growth of 12 native and introduced plant species from six families. We predicted that introduced species sharing an evolutionary history with these generalists might be less vulnerable than native plant species. We quantified plant and herbivore abundances within our heterogeneous site and also established herbivore removal experiments in 160 plots spanning the gamut of microhabitats. As 18 collaborators, we checked 2000 seedling sites every day for three weeks to assess nocturnal seedling predation. Laboratory feeding trials allowed us to quantify the palatability of plant species to the two dominant nocturnal herbivores at the site (slugs and earwigs) and allowed us to account for herbivore microhabitat preferences when analyzing attack rates on seedlings. The relationship between local slug abundance and percent cover of five common plant taxa at the field site was significantly negatively associated with the mean palatability of these taxa to slugs in laboratory trials. Moreover, seedling mortality of 12 species in open‐field plots was positively correlated with mean palatability of these taxa to both slugs and earwigs in laboratory trials. Counter to expectations, seedlings of native species were neither more vulnerable nor more palatable to nocturnal generalists than those of introduced species. Growth comparison of plants within and outside herbivore exclosures also revealed no differences between native and introduced plant species, despite large impacts of herbivores on growth. Cryptic nocturnal predation on seedlings was common and had large effects on plant establishment at our site. Without intensive monitoring, such predation could easily be misconstrued as poor seedling emergence.

Population genetics and conservation of the threatened southeastern beach mouse (Peromyscus polionotus niveiventris): subspecies and evolutionary units - Jacob F. Degner; I. Jack Stout; James D. Roth; Christopher L. Parkinson (Conservation Genetics, 2007)

Quantifying the effects of voluntary contraction and inter-stimulus interval on the human soleus H-reflex - Richard B. Stein; Kristen L. Estabrooks; Steven McGie; Michael J. Roth; Kelvin E. Jones (Experimental Brain Research, 2007)

Pharmacokinetics in mice implanted with xenografted tumors after intravenous administration of tasidotin (ILX651) or its carboxylate metabolite - Peter L. Bonate; David Beyerlein; Jennifer Crawford; Stephanie Roth; Roy Krumbholz; Steve Schmid (The AAPS Journal, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Microglial Activation is Required for Aβ Clearance After Intracranial Injection of Lipopolysaccharide in APP Transgenic Mice - Donna L. Herber; Mary Mercer; Lisa M. Roth; Keisha Symmonds; Jessica Maloney; Nedda Wilson; Melissa J. Freeman; Dave Morgan; Marcia N. Gordon (Journal of Neuroimmune Pharmacology, 2007)

The predatory behavior of wintering Accipiter hawks: temporal patterns in activity of predators and prey - Timothy C. Roth; Steven L. Lima (Oecologia, 2007)

Reciprocal Relationships Between Exotic Rusty Crayfish, Macrophytes, and Lepomis Species in Northern Wisconsin Lakes - Brian M. Roth; Jakob C. Tetzlaff; Mara L. Alexander; James F. Kitchell (Ecosystems, 2007)

Temporal dynamics of the urban heat island of Singapore - Winston T. L. Chow; Matthias Roth (International Journal of Climatology, 2006)

WAY-100635 is a potent dopamine D4 receptor agonist - Benjamin R. Chemel; Bryan L. Roth; Blaine Armbruster; Val J. Watts; David E. Nichols (Psychopharmacology, 2006)

Determinants of predation risk in small wintering birds: the hawk’s perspective - Timothy C. Roth; Steven L. Lima; William E. Vetter (Behavioral Ecology and Sociobiology, 2006)

Use of anatomical and kinetic models in the evaluation of human food additive safety - William L. Roth (The AAPS Journal, 2005)

The highly efficacious actions of N-desmethylclozapine at muscarinic receptors are unique and not a common property of either typical or atypical antipsychotic drugs: is M1 agonism a pre-requisite for mimicking clozapine?s actions? - Marilyn A. Davies; Beth Ann Compton-Toth; Sandra J. Hufeisen; Herbert Y. Meltzer; Bryan L. Roth (Psychopharmacology, 2005)

5-ZATRYPTAMINE ANALOGS AS h5-HT6 SEROTONIN RECEPTOR LIGANDS - Manik Pullagurla; Małgorzata Dukat; Bryan L. Roth; Vincent Setola; Richard A. Glennon (Medicinal Chemistry Research, 2005)

The economic value of recreational fisheries in Nordic countries - A.‐L. Toivonen; E. Roth; S. Navrud; G. Gudbergsson; H. Appelblad; B. Bengtsson; P. Tuunainen (Fisheries Management and Ecology, 2004)
Recreational fishing, whether free or at cost, has an economic value. This value was measured in five Nordic countries based on a contingent valuation mail survey. Regression models were used to identify demographic characteristics, types of fishing patterns and differences in the countries’ management regimes that can explain both actual fishing expenditure and willingness to pay for the non‐market benefits by persons participating in fishing or enjoying the benefits derived by it. Net benefit, i.e. willingness to pay over and above actual expenditure was highest amongst those fishing. In Denmark, the small number of generalist fishermen get the highest benefit. In Finland results are mixed but sports fishermen benefit on average even more than generalists. Urban sports fishing raises the highest benefit in Iceland while in Norway the benefit is more equally spread, with occasional anglers and women reaping the least. In Sweden the mean benefit is the lowest in the Nordic countries but evenly distributed among categories of fishermen. In the Nordic countries combined, nationality explains willingness to pay as being Norwegian or Finnish increases benefit and being Icelandic reduces it. The non‐use value of recreational fisheries was elicited through posing questions on willingness to pay for the preservation of the existence of current fish stocks and current quality of recreational fishing to persons participating in fishing or enjoying the benefits derived from it. For those not fishing or people in general, the power of the models to explain willingness to pay for the existence of recreational fisheries was very weak. The benefit, i.e. willingness to pay, is higher if somebody in the household fishes. Educated, young, urban, well‐off citizens also put value on the non‐use of the resource.

Water flow and solute transport in furrow-irrigated fields - Fariborz Abbasi; Jan Feyen; Robert L. Roth; Mike Sheedy; M. T. van Genuchten (Irrigation Science, 2003)

Differences in chondroitin AC lyase activity of Flavobacterium columnare isolates - K M Stringer‐Roth; W Yunghans; L F Caslake (Journal of Fish Diseases, 2002)

In vitro receptor screening of pure constituents of St. John's wort reveals novel interactions with a number of GPCRs - Veronika Butterweck; Adolf Nahrstedt; Jon Evans; Sandy Hufeisen; Laura Rauser; Jason Savage; Beth Popadak; Paul Ernsberger; Bryan L. Roth (Psychopharmacology, 2002)

Microbial reduction of Fe(III) in the presence of oxygen under low pH conditions - Kirsten Küsel; Ursula Roth; Harold L. Drake (Environmental Microbiology, 2002)
Summary In acidic, coal mining lake sediments, facultatively anaerobic Acidiphilium species are probably involved in the reduction of Fe(III). Previous results indicate that these bacteria can co‐respire O 2 and Fe(III). In this study, we investigated the capacity of the sediment microbiota to reduce Fe(III) in the presence of O 2 at pH 3. In sediment microcosms with 4% O 2 in the headspace, the concentration of Fe(II) increased at a rate of 1.03 μmol (g wet sediment) − 1 day − 1 within the first 7 days of incubation which was similar to the rate obtained with controls incubated under anoxic conditions. However, in microcosms incubated under air, Fe(II) was consumed after a lag phase of 8 h with a rate of 2.66 μmol (g wet sediment) − 1 day − 1 . Acidiphilium cryptum JF‐5, isolated from this sediment, reduced soluble Fe(III) with either 4 or 21% O 2 in the headspace, and concomitantly consumed O 2 . However, the rate of Fe(II) formation normalized for cell density decreased under oxic conditions. Schwertmannite, the predominant Fe(III)‐mineral of this sediment, was also reduced by A. cryptum JF‐5 under oxic conditions. The rate of Fe(II) formation by A. cryptum JF‐5 decreased after transfer from preincubation under air in medium lacking Fe(III). Acidiphilium cryptum JF‐5 did not form Fe(II) when preincubated under air and transferred to anoxic medium containing Fe(III) and chloramphenicol, an inhibitor of protein synthesis. These results indicate that: (i) the reduction of Fe(III) can occur at low O 2 concentrations in acidic sediments; (ii) Fe(II) can be oxidized at O 2 concentrations near saturation; and (iii) the enzyme(s) responsible for the reduction of Fe(III) in A. cryptum JF‐5 are not constitutive.

plastids undifferentiated, a nuclear mutation that disrupts plastid differentiation in Zea mays L. - Ronelle Roth; Ruairidh J. Sawers; Helen L. Munn; Jane A. Langdale (Planta, 2001)

Methodological, conceptual and sampling practices in surveying recreational fisheries in the Nordic countries - experiences of a valuation survey - E. Roth; A. L. Toivonen; S. Navrud; B. Bengtsson; G. Gudbergsson; P. Tuunainen; H. Appelblad; G. Weissglas (Fisheries Management and Ecology, 2001)

Methodological, conceptual and sampling practices in surveying recreational fisheries in the Nordic countries – experiences of a valuation survey - E. Roth; A. L. Toivonen; S. Navrud; B. Bengtsson; G. Gudbergsson; P. Tuunainen; H. Appelblad; G. Weissglas (Fisheries Management and Ecology, 2001)
The planning and initial phases of a joint Nordic project for the valuation of recreational fisheries is described. The economic value of recreational fisheries was taken to include non‐market value as well as the traditional market value. The design of the survey was similar for each country so as to facilitate future comparison. However, initially there were difficulties in defining categories of recreational fishermen in the different countries. Other background information also had to be adapted to national circumstances. National population registers were used as the sampling frames. The effect of this on the responses from a valuation survey is discussed. Accessibility to population register data varies by country and so do possibilities for random sampling. Legal constraints were faced when implementing a centralised mailing system.

Expression of liver fatty acid binding protein alters growth and differentiation of embryonic stem cells - Friedhelm Schroeder; Barbara P. Atshaves; Olga Starodub; Amy L. Boedeker; Roger R. Smith; John B. Roths; William B. Foxworth; Ann B. Kier (Molecular and Cellular Biochemistry, 2001)

Genotypic variation in response of quaking aspen (Populus tremuloides) to atmospheric CO2 enrichment - Richard L. Lindroth; Sherry Roth; Erik V. Nordheim (Oecologia, 2001)

Interaction of cholera toxin and Escherichia coli heat-labile enterotoxin with glycoconjugates from rabbit intestinal brush border membranes: Relationship with ABH blood group determinants - Luis E. Balanzino; José L. Barra; Estela M. Galváin; German A. Roth; Clara G. Monferran (Molecular and Cellular Biochemistry, 1999)

A comparison of estimated and calculated effective porosity - Daniel B. Stephens; Kuo-Chin Hsu; Mark A. Prieksat; Mark D. Ankeny; Neil Blandford; Tracy L. Roth; James A. Kelsey; Julia R. Whitworth (Hydrogeology Journal, 1998)

Maryland Biological Stream Survey: Development of a Fish Index of Biotic Integrity - N. Roth; M. Southerland; J. Chaillou; R. Klauda; P. Kazyak; S. Stranko; S. Weisberg; L. Hall; R. Morgan II (Environmental Monitoring and Assessment, 1998)

Preliminary Studies on the Population Genetics of the Central Stoneroller (Campostoma anomalum) from the Great Miami River Basin, Ohio - R. N. Silbiger; S. A. Christ; A. C. Leonard; M. Garg; D. L. Lattier; S. Dawes; P. Dimsoski; F. McCormick; T. Wessendarp; D. A. Gordon; A.C. Roth; M. K. Smith; et al. (Environmental Monitoring and Assessment, 1998)

Enriched atmospheric CO 2 and defoliation: effects on tree chemistry and insect performance - Sherry Roth; Richard L. Lindroth; John. C. Volin; Eric. L. Kruger (Global Change Biology, 1998)
We examined the effects of CO 2 and defoliation on tree chemistry and performance of the forest tent caterpillar , Malacosoma disstria . Quaking aspen ( Populus tremuloides ) and sugar maple ( Acer saccharum ) trees were grown in open‐top chambers under ambient or elevated concentrations of CO 2 . During the second year of growth, half of the trees were exposed to free‐feeding forest tent caterpillars, while the remaining trees served as nondefoliated controls. Foliage was collected weekly for phytochemical analysis. Insect performance was evaluated on foliage from each of the treatments. At the sampling date coincident with insect bioassays, levels of foliar nitrogen and starch were lower and higher, respectively, in high CO 2 foliage, and this trend persisted throughout the study. CO 2 ‐mediated increases in secondary compounds were observed for condensed tannins in aspen and gallotannins in maple. Defoliation reduced levels of water and nitrogen in aspen but had no effect on primary metabolites in maple. Similarly, defoliation induced accumulations of secondary compounds in aspen but not in maple. Larvae fed foliage from the enriched CO 2 or defoliated treatments exhibited reduced growth and food processing efficiencies, relative to larvae on ambient CO 2 or nondefoliated diets, but the patterns were host species‐specific. Overall, CO 2 and defoliation appeared to exert independent effects on foliar chemistry and forest tent caterpillar performance.

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Behavioral ecology ofMyiopharus doryphorae (riley) andM. aberrans (townsend), tachinid parasitoids of the colorado potato beetle - E. R. López; L. C. Roth; D. N. Ferro; D. Hosmer; A. Mafra-Neto (Journal of Insect Behavior, 1997)

A theoretical comparison of electric and magnetic stimulation of the brain - J. M. Saypol; B. J. Roth; L. G. Cohen; M. Hallett (Annals of Biomedical Engineering, 1992)

A comparison of two models for calculating the electrical potential in skeletal muscle - Bradley J. Roth; Frans L. H. Gielen (Annals of Biomedical Engineering, 1987)

Ultrastructure of the capsule of Klebsiella pneumoniae and slime of Enterobacter aerogenes revealed by freeze etching - E. Louise Springer; Ivan L. Roth (Archives of Microbiology, 1973)